Need for an Artificial Intelligence-based Diabetes Care Management System in India and the United States - Veena Mayya; Rajesh N.V.P.S. Kandala; Varadraj Gurupur; Christian King; Giang T. Vu; Thomas T.H. Wan (Health Services Research & Managerial Epidemiology, 2024)
Objective Diabetes mellitus is an important chronic disease that is prevalent around the world. Different countries and diverse cultures use varying approaches to dealing with this chronic condition. Also, with the advancement of computation and automated decision-making, many tools and technologies are now available to patients suffering from this disease. In this work, the investigators attempt to analyze approaches taken towards managing this illness in India and the United States. Methods In this work, the investigators have used available literature and data to compare the use of artificial intelligence in diabetes management. Findings The article provides key insights to comparison of diabetes management in terms of the nature of the healthcare system, availability, electronic health records, cultural factors, data privacy, affordability, and other important variables. Interestingly, variables such as quality of electronic health records, and cultural factors are key impediments in implementing an efficiency-driven management system for dealing with this chronic disease. Conclusion The article adds to the body of knowledge associated with the management of this disease, establishing a critical need for using artificial intelligence in diabetes care management.